Body as disease. (17th October 2022) - Oh, David C.
ABSTRACT: The essay is a reflection on my experience of isolation on campus as my body was marked as a carrier of disease. Locating the essay in the literature about fears of Asian Americans as an alien presence and a yellow peril threat and on the work on microaggressions in academia, I understand my colleagues' avoidance as rooted in racialized fears of COVID-19. This demonstrates the problems of colorblind racism and the limits of allyship. Through connecting the BLM protests and COVID-19, the shared risk to Black and Asian American bodies becomes highly salient, and it points to an opportunity for Black-Asian solidarity that can present a substantive challenge to White supremacy.